2021
DOI: 10.1371/journal.pone.0249168
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and associated factors towards inpatient health care services among adult patients at Pawie General Hospital, West Ethiopia

Abstract: Introduction Improving the quality of services is the primary goal of the Ethiopia reform program to satisfy patients. Patient satisfaction is an attitude resulting from a person’s general orientation towards a total experience of health care. According to world health organization consumer satisfaction is playing an increasingly important role in the quality of care reforms and health-care delivery more generally. Objective To assess patient’s satisfaction and associated factors with health care services am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
(22 reference statements)
0
8
3
Order By: Relevance
“…The difference could be due to the variation in the level of need and expectations for nursing care services. This study's ndings, however, are lower than those of studies conducted in England (60%) (16) and Pawie General Hospital in Benishangul Gumuze Region, West Ethiopia (68.8%) (17). The difference could be due to the subjective nature of satisfaction and/or study, may be due to the difference in the operationalization of satisfaction and the techniques to determine satisfaction status.…”
Section: Discussioncontrasting
confidence: 77%
“…The difference could be due to the variation in the level of need and expectations for nursing care services. This study's ndings, however, are lower than those of studies conducted in England (60%) (16) and Pawie General Hospital in Benishangul Gumuze Region, West Ethiopia (68.8%) (17). The difference could be due to the subjective nature of satisfaction and/or study, may be due to the difference in the operationalization of satisfaction and the techniques to determine satisfaction status.…”
Section: Discussioncontrasting
confidence: 77%
“…The outpatient satisfaction (53.3%) was low when compared to previous studies on inpatients which ranged from 60% to more than 90% [ 1 , 15 , 20 ]. This low rate may be explained by the short time using healthcare services and the day-time treatment service.…”
Section: Discussioncontrasting
confidence: 65%
“…By summing up the response of 39 questions, the scores more than or equal to the mean score were categorized as satisfied and those less than the mean were categorized as unsatisfied. So, the mean score was used as the cut-off value [ 15 ]. The independent variables include socio-demographic characteristics such as age, gender, education, occupation, economic status, and health insurance status.…”
Section: Methodsmentioning
confidence: 99%
“…An evaluation of patient satisfaction with service provided in the health care system has been globally recognized as the measure of health care service quality. [22][23][24] However, there is a lack of research findings that indicate patient satisfaction with newly implemented PC service, particularly in developing countries including Ethiopia. In addition, it has recently been suggested that the quality of PC is closely linked to patient satisfaction as it will affect therapeutic outcome and patient retentions.…”
Section: Discussionmentioning
confidence: 99%
“…21 The evaluation of patient's satisfaction, an integral healthcare quality component, is a very important indicator of quality assessment in a health care system as it offers information on the provider's success at meeting the expectations of most relevance to the client and a key determinant of patients' perspective behavioural intention. [22][23][24] In Ethiopia, PC service has been newly implemented in different public hospitals in which Jimma University Medical Center is a pioneer in launching of the service. 25 Currently, in accordance with the National Clinical Pharmacy Service Directive developed by the Federal Ministry of Health of Ethiopia, PC services are being provided by clinical pharmacists, which includes patient assessment, developing care plan, and follow up and evaluation for continuous care of patients.…”
Section: Introductionmentioning
confidence: 99%